2022
DOI: 10.1002/ldr.4265
|View full text |Cite
|
Sign up to set email alerts
|

Study on restoring abandoned mine lands to economically usable state using the post‐occupancy evaluation method

Abstract: Abandoned mine lands are a common element of the contemporary landscape. In administrative practice, they are rated low, yet they are of interest to informal users and scientific and cultural communities. The aim of our research was to identify the possibilities of using qualitative research methods, applied in architecture, to create friendly, urban spaces with a universal character in the areas of abandoned quarries.The study was conducted in the Sadowa G ora quarry area in southern Poland, using the post oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The main drivers of land degradation are deforestation and inappropriate land use practices and also lack of comprehensive plan for the eco‐development of the region. The rapid loss of forest cover and land degradation in mined sites of tropical landscapes were widely reported by several workers in the past (Joshi et al, 2006; Garai & Narayana, 2018; Guan & Yu, 2021; Thakur et al, 2022; Chećko et al, 2022). Our study also observed rehabilitation of abandoned villages, construction of colonies and expansion of road networks are further responsible for destruction of forest and agricultural landscape.…”
Section: Discussionmentioning
confidence: 82%
“…The main drivers of land degradation are deforestation and inappropriate land use practices and also lack of comprehensive plan for the eco‐development of the region. The rapid loss of forest cover and land degradation in mined sites of tropical landscapes were widely reported by several workers in the past (Joshi et al, 2006; Garai & Narayana, 2018; Guan & Yu, 2021; Thakur et al, 2022; Chećko et al, 2022). Our study also observed rehabilitation of abandoned villages, construction of colonies and expansion of road networks are further responsible for destruction of forest and agricultural landscape.…”
Section: Discussionmentioning
confidence: 82%
“…Koźma, 2011), the lake to be, has great potential for the development of recreation, water tourism (including diving) and geotourism. The well-known Polish examples of the adaptation of abandoned quarries for geo-educational purposes (e.g., Geosfera in Jaworzno; Chećko et al, 2022, the European Centre for Geological Education on Góra Rzepka in Chęciny https://www.eceg.uw.edu.pl/en/ or the Centre of Geoeducation of the Świętokrzyski Geopark http://geonaturakielce.pl/centrum_geo/) can certainly inspire local authorities to build such a facility in the Pałuki area.…”
Section: Possibilities For the Development Of Geotourismmentioning
confidence: 99%
“…in the Upper Silesian Coal Basin in Poland - Gaidzik and Chmielewska, 2020), natural areas (e.g., in the German-Polish UNESCO Global Geopark Muskau Arch https://www.muskau-arch.eu/ -Koźma, 2011) geoeducational areas (e.g. Koźma, 2011; in the Sadowa Góra quarry area in southern Poland https://www.jaworzno.pl/osrodekedukacji-ekologiczno-geologicznej-geosfera/ - Chećko et al, 2022) and geotourism (e.g. in the Świętokrzyskie Mountains in the central Poland -Pabian, 2015;in southern Ecuador -Carrión-Mero, 2021; on the Serifos Island in Greece - Vlachopoulos and Voudouris, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of reclamation of territories damaged by mining enterprises has been raised for a long time. Both quarries and heaps cause significant damage to both the environment and the economy of the state [7]. Therefore, today in world practice there is a whole range of measures that are aimed at restoring and improving the natural conditions of man-madedisturbed territories [8].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%